From Identification to Insight: Making Full Use of the Diagnostic Potential of MS/MS Proteotyping in Clinical Microbiology Using Efficient Bioinformatics - Muth, Thilo; Karlsson, Roger; Yu, Yi-Kuo; Alves, Gelio (Journal of proteome research, 2025)
Accurate and rapid pathogen identification is critical for modern diagnostics, driving the need for technologies that combine speed, specificity, and functional insight. In this context, mass spectrometry (MS)-based proteomics is rapidly emerging as a transformative approach in clinical microbiology, offering comprehensive characterization of microorganisms and direct identification of protein biomarkers relevant to infectious disease diagnostics. While MS1-based approaches such as MALDI-TOF Biotyper have revolutionized species-level microbial identification through rapid and cost-effective workflows, they remain fundamentally limited in resolving strain-level differences and in detecting antimicrobial resistance (AMR) determinants. In contrast, so-called proteotyping enables the identification of organisms and resistance-associated proteins based on peptide sequence information obtained by tandem mass spectrometry (MS/MS), most commonly using shotgun proteomics. However, the clinical utility of proteotyping depends on the availability of efficient and accurate bioinformatics tools capable of handling large databases, disambiguating shared peptide sequences, and providing taxonomic and functional assignments with clinical relevance. This perspective highlights the diagnostic potential of MS/MS proteotyping and argues that advances in bioinformatics pipelines are needed for moving from microbial identification to actionable clinical insight.